THE POSITION OF EDUCATION IN THE SOCIETY (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
It is clearly evident that, the role of education in the every cite of society is developing day by day. Education is a human right and is central to achieving many other sustainable development outcomes and incomes .